Ethics and medicine - Shair Mohamad, Mohd Akram (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
This paper provides a brief overview of competing ethical approaches to various substantial legal issues in a Medical or Healthcare context. In a nutshell, there are three main reasons for considering ethical approaches separately from and prior to examining the law. This is because many of the legal principles in medical law are based on ethical foundations, for example the law on consent to treatment is based on respect for autonomy. Secondly, on many of the topics in medical law, law is insufficiently developed to provide guidance for healthcare professionals, e.g. the equitable remedy for breach of confidentiality. And thirdly, there may be ethical reasons for not attempting to extend law into certain areas, e.g. attempts to regulate the behavior of pregnant women which may be better influenced by education and information, rather than law.